Front Cover: Azoliums and Ag(I)‐N‐Heterocyclic Carbene Thioglycosides: Synthesis, Reactivity and Bioactivity (Eur. J. Org. Chem. 9/2022). Issue 9 (21st February 2022) - Ryzhakov, Dmytro; Beillard, Audrey; Le Bideau, Franck; Al‐Shuaeeb, Riyadh Ahmed Atto; Alami, Mouad; Bantreil, Xavier; Bonnemoy, Aurore; Gautier, Arnaud; Lamaty, Frédéric; Messaoudi, Samir
Abstract : The Front Cover shows a desert with cactuses where the Ag(I)‐NHC‐thioglycosides are wanted. With the help of Pd‐catalysis and mechanochemistry, this target has been reached. Cover design by Dmytro Ryzhakov. More information can be found in the Research Article by A. Gautier, F. Lamaty, S. Messaoudi et al .